Lead & influence : - Fritz, Mark (John Wiley & Sons, 2014)
Lead & Influence explains how to use the power of ownership to become even more successful in leading your organization. Based on thirty years of leading and influencing across distances and cultures, author Mark Fritz has identified key leadership mindsets and habits that create a culture of ownership. It begins with a leader's personal ownership. Second, it's about enabling personal ownership in others. Third, it's about enabling team and organizational ownership. Why? Because you want your people to not just do their job, but also to own the achievement (the outcomes). Explains how executives and managers can successfully lead across distances and cultures Author Mark Fritz is an international speaker focused on helping executives and managers successfully lead across distances and cultures ...and still have a life A leader's performance and quality of life is in direct proportion to the level of ownership their people to deliver the results. The more ownership your people take, the more success you and your organization will enjoy. Lead &​ Influence will show you how to empower your employees to own achievement, no matter the distance between you and them.